Sintered Fe-Ni-Si-C alloys - Tiwat Kaewkam; Panya Kansuwan; Naoto Ohtake; Pongsak Wila; Rungtip Krataithong; Nattaya Tosangthum; Thanyaporn Yotkaew; Ruangdaj Tongsri (IOP Conference Series Materials Science and Engineering, 2021)
Abstract The aim of this research is to explore the effect of nickel content on microstructural development and mechanical properties of sintered Fe-Ni-Si-C alloys. The sintered alloys were prepared from powder mixtures of pre-alloyed Fe-Ni-based powders (nickel contents varied as 0.45, 0.90, 1.80, and 4.00 wt.%) and fixed 4 wt.% silicon carbide powder by using a powder metallurgical process. Sintering was performed in a vacuum furnace at 1250°C for 45 minutes and slow cooling in the furnace. Microstructures of sintered alloys varied with nickel contents. Nickel showed a strong influence on promoting bainitic ferrite/martensite-austenite (BF/M-A) structure formation. Retained austenite in BF/M-A structure was found to increase with increasing nickel content. Tensile properties (strength and elongation value) of sintered alloys increased with increasing nickel content.
Keywords: Metal Alloys Wear and Properties; Powder Metallurgy Techniques and Materials; Microstructure and Mechanical Properties of Steels